Naturressursene i Antarktis - Antonsen, Per (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser

A forgotten explorer: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polar Record, 1974)
Keywords: Antarktis; biografi; ekspedisjoner; forskning; oppdagelsesreiser

Fra tjuagutt til sydpolfarer - Gran, Tryggve (Mortensen, 1974)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Some notes on the future of the Antarctic Treaty collaboration - Hambro, Edvard (American journal of international law, 1974)
politikk jus
Keywords: Antarktis

Kappløpet - Holt, Kåre (Gyldendal, 1974)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; biografier; fortellinger; oppdagelsesreiser

The South Pole - Mountfield, David (A history of polar exploration, 1974)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Glaciological studies in the South Shetland Islands - Orheim, Olav (Antarctic Journal of the United States, 1974)
Keywords: Antarktis; Sør-Shetlandsøyene; geofysikk; glasiologi

Antarktis i sikkerhetspolitisk perspektiv - Skagestad, Odd Gunnar (Internasjonal politikk, 1974)
Keywords: Antarktis; politikk

Vitenskapelig utforskning som internasjonalt samarbeidsprosjekt i polarområdene - Skagestad, Odd Gunnar (Stiftelsen, 1974)
Keywords: Antarktis; forskning; jus; politikk

The New Development in the Polar Regions - Sollie, Finn (Cooperation and Conflict, 1974)
Due to factors connected with modern technological developments and with the increasing global demand for new sources of raw materials, there is today a growing interest in the possibilities for economic exploitation of the polar regions. This makes for a new development in these regions; a development comprising and affecting such fields as science and technology as well as economy, transportation, military strategy and ecology. The present paper discusses this new development and its implications in an international perspective. Special attention is paid to the significance - in the physical/ geographical sense and otherwise - of the polar regions in the global context. A special section deals, on a general level, with 'the problem of the new territories', and the polar regions are discussed as new territories. Pointing out the risks and dangers inherent in the present and emerging developments, the author emphasizes the need for action, especially international cooperation, to meet and solve such problems. Cooperation may be facilitated through regular consultations between the states concerned, as is the case under the Antarctic Treaty. For the Arctic in particular, the author suggests a distinction between three basic zones (viz. the 'Central' the 'Intermediate' and the 'National' Arctic) as a possible point of departure for future discussion of measures of international cooperation.
Keywords: Antarktis; internasjonal politikk; polarområdene

Antarktis og den internasjonale havbunnsorganisasjon - Traavik, Kim (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; havbunnen; havrett; internasjonal; politikk; ressurser; rett